Pengenalan PLTS Kepada Pelajar Untuk Menumbuhkan Minat Terhadap Pengembangan Energi Terbarukan - Tunggal Prasetiyo, Dani Hari; Baihaqi, Mas Ahmad; Supraptiningsih, Linda Kurnia; Wahyudi, Djoko; Muhammad, Alief; Fathuddin Noor, Muhammad; Yulyawan, Eva Kurnia (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2022)
Technological developments and increasing population have created various problems, one of which is the energy sector. Indonesia has considerable potential to develop and exploit the potential of sunlight which can be converted into electrical energy. However, these efforts cannot run well if human resources (HR) do not understand the working system of solar power plants (PLTS). Therefore, efforts are needed to introduce and explore the potential of existing human resources. The target object of community service activities is carried out to junior high school students. PLTS is an interesting technology to convey to teenagers. Besides being able to arouse curiosity about PLTS, teenagers can also provide innovations in PLTS technology. Participants were enthusiastic when participating in the event and understood various types of renewable energy and renewable energy sources and understood the working system of solar panels.